2019
DOI: 10.3390/ijerph16071181
|View full text |Cite
|
Sign up to set email alerts
|

Food Cravings and Eating: The Role of Experiential Avoidance

Abstract: Food cravings have been associated with problematic eating behaviors, such as emotional eating. Late adolescence is an important developmental period to examine this association, as late adolescents have greater independence in food choices as well as potentially higher demands during a transitional period of their lives. Mechanisms underlying the association between food cravings and problematic eating remain unclear. This study examined whether experiential avoidance (EA) may be one possible mechanism mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 54 publications
2
5
0
2
Order By: Relevance
“…Given this factorial solution, the Acceptance items content referred to the elimination, control, or modification of thoughts or urges related to food craving. This content would correspond with the lack of acceptance as explained in the literature (Hayes et al, 2006), emphasizing that these experiences are perceived as unwanted (Fahrenkamp et al, 2019).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Given this factorial solution, the Acceptance items content referred to the elimination, control, or modification of thoughts or urges related to food craving. This content would correspond with the lack of acceptance as explained in the literature (Hayes et al, 2006), emphasizing that these experiences are perceived as unwanted (Fahrenkamp et al, 2019).…”
Section: Discussionmentioning
confidence: 63%
“…Food cravings are often experienced as unwanted. It has been suggested that food cravings may involve intrusive thoughts, and therefore individuals may choose to engage in ingesting food to avoid this unpleasant sensation (Fahrenkamp et al, 2019 ). In this sense, it seems that the theoretical approach of psychological flexibility from the Acceptance and Commitment Therapy (ACT) could be interesting in the explanation of food cravings and eating behavior (Juarascio et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reactivity to food cues and impulsivity may lead to abnormal eating behaviours. 42 Eating disorders are characterized by excessive (Bahvaashinam/ Bahu Bhuk/ Bahusha Yachantam/Annapaana Ratim/ Lolam Kshudhadhikam/Kshudaatura) or insufficient food intake (Bhojana Anabhilaashinam/Anannabhilasha/Arochaka/Aahaara Dveshinam/ Anna Dveshinam/Alpaahaara/Na Kshuda). Anorexia nervosa, Bulimia nervosa, and binge eating are the most common forms of eating disorder.…”
Section: Abnormal Eating Behaviours and Bhutonmadamentioning
confidence: 99%
“…Terkait kebiasaan makan, remaja akhir memiliki otonomi lebih dalam mengatur asupan makanannya dan menunjukkan lebih banyak kesulitan dalam pengaturan perilaku makan (Fahrenkamp et al, 2019). Masalah yang terkait dengan konsumsi pangan pada remaja akhir yaitu, tidak peduli terhadap pemilihan makanan yang dikonsumsi, mengkonsumsi makanan yang terlalu banyak, konsumsi makanan yang mengikuti trend masa kini tanpa memprioritaskan kebutuhan gizi, dan lupa waktu makan karena banyaknya aktivitas (Moehji, 2017).…”
Section: Pendahuluanunclassified